Organizational Initiatives for Promoting Employee Work-Life Reconciliation Over the Life Course. A Systematic Review of Intervention Studies - Ropponen, Annina; Känsälä, Marja; Rantanen, Johanna; Toppinen-Tanner, Salla (Nordic Journal of Working Life Studies, 2016)
This review aimed to explore the initiatives, interventions, and experiments implemented by employing organizations and designed to support the work-life reconciliation at workplaces, and the effects of these actions on employees’ well-being at work. A systematic literature review was conducted on the basis of a search in PsycInfo, ERIC, and the ISI Web of Science database of Social Sciences between January 2000 and May 2015. Those studies were included in which either organizational or individual-level initiatives, interventions, or experiments were implemented by employers at workplaces in order to promote the work-life reconciliation of their employees. Work-life reconciliation was considered to encompass all life domains and all career stages from early to the end of working career. The content analysis of 11 studies showed that effective employer actions focused on working time, care arrangements, and training for supervisors and employees. Flexibility, in terms of both working time and other arrangements provided for employees, and support from supervisors decreased work-family conflict, improved physical health and job satisfaction, and also reduced the number of absence days and turnover intentions. Overall, very few intervention studies exist investigating the effects of employer-induced work-life initiatives. One should particularly note the conditions under which interventions are most successful, since many contextual and individual-level factors influence the effects of organizational initiatives on employee and organizational outcomes.